3D FEM Model on the Parameters’ Influence of EPB-TBM on Settlements of Single and Twin Metro Tunnels During Construction - Masoud Forsat (14158980) (2022)
The present research exposes the investigation on three-dimensional modeling of the single and twin metro tunnels for the case of the Tehran metro line. At first, simulation implemented on the comparison of the ground movements in the single and twin tunnels. Then the simulation has been performed on the influence of effective parameters of EPB-TBM on the surface settlements throughout excavation. The overcutting, shield conicity, grouting, and the final lining system modeled and the influence of face supporting pressure, grout injection pressure, as well as the clear distance of the tunnels, has been analyzed. The initial results showed a valid ground settlement behavior. The maximum settlements occurred at the end of the shield tail and it was higher in the single tunnel. The face supporting pressure had more effect on the surface settlement in comparison to the grout injection pressure. By increasing the face pressure in the single tunnel, the place of maximum settlement moved back while the grout pressure is insignificant for decreasing the settlements. Furthermore, the influence of the clear distance in the twin tunnels led to zero after the length of 30 m. Accordingly, for more distances, the tunnels must be examined independently and as two different single tunnels. Other Information Published in: International Journal of Pavement Research and Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42947-021-00034-0